2021
DOI: 10.4037/ccn2021556
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Volume-Based Feeding to Optimize Delivery of Enteral Nutrition

Abstract: Background At least 80% of ordered enteral nutrition should be delivered to improve outcomes in critical care patients. However, these patients typically receive 60% to 70% of ordered enteral nutrition volume. In a practice review within a 28-bed medical-surgical adult intensive care unit, patients received a median of 67.5% of ordered enteral nutrition with standard rate-based feeding. Volume-based feeding is recommended to deliver adequate enteral nutrition to critically ill patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…38 Soguel et al 39 found that teaching and continuous training provided by a nutritionist dedicated to the ICU, combined with the implementation of an optimized EN protocol, could improve the energy intake of critically ill patients by approximately 32%. Bonomo et al 40 observed an increase in the volume of EN provided to critically ill patients through the creation of protocols and training of HCPs through the teaching, demonstration, active involvement, and dissemination of educational materials.…”
Section: Discussionmentioning
confidence: 99%
“…38 Soguel et al 39 found that teaching and continuous training provided by a nutritionist dedicated to the ICU, combined with the implementation of an optimized EN protocol, could improve the energy intake of critically ill patients by approximately 32%. Bonomo et al 40 observed an increase in the volume of EN provided to critically ill patients through the creation of protocols and training of HCPs through the teaching, demonstration, active involvement, and dissemination of educational materials.…”
Section: Discussionmentioning
confidence: 99%
“…Whenever adopted into clinical practice, this approach has seen substantial improvements in the mean and median volumes of enteral nutrition delivered to patients [47 ▪▪ ,48,49]. For example, Bonomo et al [47 ▪▪ ] in 2021 adopted this approach in a study of 73 patients admitted to critical care and were able to achieve a median rate of delivery of 99.8% of ordered volume of enteral nutrition. Adopting such new practices can be a challenge; however, a study from 2020 used quality improvement methodology to implement change subsequently demonstrated that more patients on a volume-based regime received adequate nutrition than those on rate-based feeding during the first crucial 7 days of nutrition support.…”
Section: Interruption Tolerance and Delivery Of Enteral Nutritionmentioning
confidence: 99%
“…This represents a shift from an hourly rate target of enteral nutrition to a 24 h volume goal, therefore, limiting calorie and protein deficit [34]. Whenever adopted into clinical practice, this approach has seen substantial improvements in the mean and median volumes of enteral nutrition delivered to patients [47 ▪▪ ,48,49]. For example, Bonomo et al [47 ▪▪ ] in 2021 adopted this approach in a study of 73 patients admitted to critical care and were able to achieve a median rate of delivery of 99.8% of ordered volume of enteral nutrition.…”
Section: Interruption Tolerance and Delivery Of Enteral Nutritionmentioning
confidence: 99%